Deference and Diffèrance: Judicial Review and the Perfect Gift - J De Ville (Potchefstroom Electronic Law Journal, 2006)
The highest courts in both Canada and South Africa have expressed themselves in favour of an approach of deference as respect in the review of administrative action. The notion of deference as respect derives from the thinking of David Dyzenhaus, who has developed a theory of democracy in support of this approach to judicial review. Dyzenhaus’ model of review attempts to steer clear from the problems he associates particularly with positivism and liberalism. Dyzenhaus’ model of review furthermore attempts to allow space for the administration to play a significant role in giving effect to democratic values, on the understanding that all such decisions need to be reasonably justifiable. In this article the views of Dyzenhaus are contrasted with those of Jacques Derrida, especially insofar as the latter has reflected on the relation between law and justice, as well as concepts such as the gift and democracy. The argument developed in this article is that Dyzenhaus’ model of review, despite its many positive features, needs to be rethought with reference to the perfect gift, unconditional justice and democracy to come. Such a rethinking is required because of the limited conception of justice – as simply ‘our’ justice – in Dyzenhaus’ model.